2014
DOI: 10.1016/j.brainres.2014.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Value-driven attentional priority signals in human basal ganglia and visual cortex

Abstract: Goal-directed and stimulus-driven factors determine attentional priority through a well defined dorsal frontal-parietal and ventral temporal-parietal network of brain regions, respectively. Recent evidence demonstrates that reward-related stimuli also have high attentional priority, independent of their physical salience and goal-relevance. The neural mechanisms underlying such value-driven attentional control are unknown. Using human functional magnetic resonance imaging, we demonstrate that the tail of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
214
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(245 citation statements)
references
References 51 publications
25
214
6
Order By: Relevance
“…Previous research on attentional control indicated that dorsal frontal-parietal brain regions are related to goal-directed attention, and ventral temporal-parietal brain regions are involved in stimulus-directed attention (Corbetta & Shulman, 2002;Serences et al, 2005). Recent studies have examined the neural mechanisms underlying value-based attention using functional magnetic resonance imaging (fMRI) and event-related potentials (ERPs) (Anderson, Laurent, & Yantis, 2015;Qi, Zeng, Ding, & Li, 2013). Anderson et al (2015) found that the tail of the caudate nucleus and extratstriate cortex were activated when the stimulus previously associated with reward was presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on attentional control indicated that dorsal frontal-parietal brain regions are related to goal-directed attention, and ventral temporal-parietal brain regions are involved in stimulus-directed attention (Corbetta & Shulman, 2002;Serences et al, 2005). Recent studies have examined the neural mechanisms underlying value-based attention using functional magnetic resonance imaging (fMRI) and event-related potentials (ERPs) (Anderson, Laurent, & Yantis, 2015;Qi, Zeng, Ding, & Li, 2013). Anderson et al (2015) found that the tail of the caudate nucleus and extratstriate cortex were activated when the stimulus previously associated with reward was presented.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the neural mechanisms underlying value-based attention using functional magnetic resonance imaging (fMRI) and event-related potentials (ERPs) (Anderson, Laurent, & Yantis, 2015;Qi, Zeng, Ding, & Li, 2013). Anderson et al (2015) found that the tail of the caudate nucleus and extratstriate cortex were activated when the stimulus previously associated with reward was presented. Qi et al (2013) found that the N2pc component was observed earlier in trials that contained the reward-associated distractor.…”
Section: Discussionmentioning
confidence: 99%
“…These initial phasic DA responses serve as alerting signals to attend appropriately to environmental stimuli and as teaching signals to learn new behavioral strategies. Especially the dorsal component of the striatum (in particular the caudate nucleus) which receives a major dopaminergic input from both the substantia nigra (NS pathway) and the VTA, has been critically implicated in alerting attention to salient stimuli and action-contingent learning (Glenn and Yang, 2012;Anderson et al, 2014a;Dang et al, 2014). When confronted with unexpected reward-feedback for a certain performed action or after a certain cue, the ensuing prediction-error in the dorsal striatum ensures that the action will be repeated or the cue attended to when similar contingencies arise (Balleine et al, 2007;Grahn et al, 2008;Glenn and Yang, 2012).…”
Section: Phasic Mesolimbic Da Reactivity In Primary Psychopathymentioning
confidence: 99%
“…Some of these regions may influence directly or indirectly visual processing, underlying reward-related modulations. Using a reward associationbased paradigm, Anderson et al (2014) demonstrated a selective activation of the extrastriate cortex but also of the caudate nucleus when previously high-rewarded visual distractor were presented in a visual search task. The caudate is a part of the basal ganglia receiving strong projections from dopaminergic pathways and connected with several associative cortical areas.…”
Section: Role Of Dopaminergic Signalsmentioning
confidence: 99%